Community perception of ecosystem services from commercially managed forests in Bhutan - Wangchuk, J.; Choden, K.; Sears, R.R.; Baral, H.; Yoezer, D.; Tamang, K.T.D.; Choden, T.; Wangdi, N.; Dorji, S.; Dukpa, D.; Tshering, K.; Thinley, C.; et al. (Elsevier, 2021)
Given the direct dependence rural communities have on forests, understanding ecosystem services can empower communities and align stakeholders to define priorities and objectives for the sustainable management of forest resources. In this qualitative study on the forest ecosystem services in Bhutan, we assessed community awareness and perceptions of local forest ecosystem services, identified their top priorities, and evaluated how they have changed over time. The study focused on state reserve forest areas designated for commercial timber production, formally known as forest management units (FMU). We held focus group discussions separately with women and men associated with five FMUs in the central belt of the country. Participants identified 45 ecosystem services, with soil productivity, freshwater, timber, fresh air, construction stone, carbon sequestration, spiritual value, pollination, and local weather regulation comprising the most highly valued services critical to local livelihood and well-being. Participants felt that forest ecosystem services have been generally declining over the past decade in the FMUs and identified a need for forest restoration activities to improve their delivery. We recommend that state forest entities conduct an awareness campaign to empower communities with the conceptual framework and globally recognized concepts to advocate for their needs related to forests. We also recommend that biophysical and economic studies be conducted in these areas to seek evidence for causal linkages between natural resource use and the status of ecosystem services. This study contributes to a growing literature on ecosystem services in Bhutan and provides a basis for future studies to understand how management activities can impact the delivery of critical services.